EARNING MANAGEMENT DETERMINANT IN INDONESIAN MANUFACTURING COMPANY - Listia, Listia; Kholilah, Kholilah; Syariati, Dian (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This study aims to provide empirical evidence regarding the effect of profitability, free cash flow, leverage, and company size on earning management in manufacturing companies. A discretionary revenue model measures earning management. This type of research is quantitative research. The population of this study is 181 manufacturing companies listed on the IDX in 2018-2021. The sampling technique uses a purposive sampling technique so that 72 samples are obtained. This study used multiple linear regression analysis to see the effect of profitability, free cash flow, leverage, and company size on earning management using SPSS 25 software. The results of hypothesis testing using the T-test prove that profitability, leverage, and company size have a positive effect on earning management. The free cash flow has a negative effect.